2020
DOI: 10.1051/bioconf/20201700253
|View full text |Cite
|
Sign up to set email alerts
|

Feed synbiotic additive to improve the productivity and quality of rabbit meat

Abstract: The study is dedicated to research into efficiency of influence of probiotic additive “Prostor” on productivity, chemical composition of meat of rabbits. The influence of synbiotic preparation “Prostor” on the population of male rabbits of hybrid form “Hypharm” of French breeding, selected at the age of 45 days. The study took place at the industrial complex of LLC “Lipetsk rabbit” in Khlevensky district of Lipetsk region. The animals were divided into control and experimental groups by the method of pairs-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…With cording to other publications modern volume of consumption of fresh vegetables, potatoes and fruits in Ukraine is 50-60% of the physiological norm. [7] Potero in storage potatoes, vegetables and fruit make up 20-30% annually. [8] Investing in storage products is 2-3 times more efficient than in the expansion of its production.…”
Section: Analysis Of Recent Research Resultsmentioning
confidence: 99%
“…With cording to other publications modern volume of consumption of fresh vegetables, potatoes and fruits in Ukraine is 50-60% of the physiological norm. [7] Potero in storage potatoes, vegetables and fruit make up 20-30% annually. [8] Investing in storage products is 2-3 times more efficient than in the expansion of its production.…”
Section: Analysis Of Recent Research Resultsmentioning
confidence: 99%
“…Synbiotics are a synergistic mixture of probiotics and prebiotics, as they support growth and survival of probiotics and boost their health benefits in the gut. Studies proved that dietary synbiotics enhanced growth performance in growing rabbits (Hassanin et al, 2015;Ali and Hassan, 2018;Kurchaeva et al, 2020;Nwachukwu et al, 2021). Kurchaeva et al (2020) reported that dietary synbiotic (1 g/kg diet) enhanced growth performance (BW and BWG), carcass traits (cooled carcass weight and dressing %), meat chemical composition (increased meat protein, Na, Ca, K, and P contents, while reduced meat fat content), meat physical traits (water-holding capacity, moisture binding capacity, fat holding capacity ability, emulsifying ability, and emulsion stability).…”
Section: Synbioticsmentioning
confidence: 99%
“…Studies proved that dietary synbiotics enhanced growth performance in growing rabbits (Hassanin et al, 2015;Ali and Hassan, 2018;Kurchaeva et al, 2020;Nwachukwu et al, 2021). Kurchaeva et al (2020) reported that dietary synbiotic (1 g/kg diet) enhanced growth performance (BW and BWG), carcass traits (cooled carcass weight and dressing %), meat chemical composition (increased meat protein, Na, Ca, K, and P contents, while reduced meat fat content), meat physical traits (water-holding capacity, moisture binding capacity, fat holding capacity ability, emulsifying ability, and emulsion stability). Similarly, Nwachukwu et al (2021) reported that dietary synbiotics (combination of 400 mg prebiotics/ kg diet + 50 mg probiotics/ kg diet) improved growth performance (final BW, BWG, and FCR) and intestinal histomorphology parameters (ileal villus height, villus width, villus density, crypt depth, and villus height: crypt depth ratio).…”
Section: Synbioticsmentioning
confidence: 99%